(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article examines the linguopragmatic characteristics of idioms in Uzbek and English, focusing on their comparative and contrastive aspects. By analyzing the underlying cultural and pragmatic elements that shape these expressions, we aim to highlight similarities and differences between the two languages. This comparative study contributes to a deeper understanding of how idioms reflect the social and cultural nuances of their respective languages.